Dyrektor szkoły – administrator, menedżer, przywódca. Między szkolną codziennością a polityką oświatową - Rosalska, Małgorzata (Wydawnictwo Naukowe UAM, 2016)
The monograph introduces current discussions on the role of the head teacher in the Polish school. It involves issues concerning leadership in education and educational leadership. Roles and tasks of head teachers are analyzed in terms of modern concepts of school management, as well as the challenges of daily school life. The book consists of two main parts. The first and theo‐retical part deals with crucial issues connected with basic research strategies in education policy and concepts of educational leadership, as well as the roles of the head teacher. The second part presents research findings on the real roles of school leaders. The study shows the complexity of tasks undertaken by head teachers and refers to current research trends in the field of education policy. The aim of this research is to identify not only how head teachers perform and perceive their roles, but also how this role is recognized and assessed those who are directly dependent on the head or cooperate with them. Opinions given by pupils, parents, teachers, local authorities and educational supervision representatives were analysed. The research conclusions can be useful in answering the question whether an educational partnership, also in terms of leadership in the broader sense, is possible in the Polish education system.

Monografia przybliża współczesne dyskusje na temat roli dyrektora szkoły. Podejmowane są w niej zagadnienia dotyczące przywództwa w edukacji i przywództwa edukacyjnego. Role i zadania dyrektorów polskich szkół analizowane są zarówno w kontekście współczesnych koncepcji zarządzania szkołami, jak i wyzwań szkolnej codzienności. Praca ukazuje złożoność zadań podejmowanych przez liderów szkolnych społeczności, a prezentowane analizy wpisują się w nurt badań usytuowanych w perspektywie polityki oświatowej. Celem badań jest rozpoznanie nie tylko w jakim zakresie dyrektorzy realizują lub postrzegają swoją rolę, ale także to, jak ta rola jest rozpoznawana i oceniana przez osoby, które są bezpośrednio zależne od dyrektora lub współpracują z nim. Analizie poddano opinie uczniów, rodziców, nauczycieli oraz przedstawicieli lokalnych samorządów i nadzoru pedagogicznego. Wnioski z badań mogą być pomocne w budowaniu odpowiedzi na pytanie, czy w polskim systemie edukacyjnym możliwe jest partnerstwo edukacyjne także w zakresie szeroko rozumianego przywództwa.
The head teacher – administrator, manager, leader. Between daily school life and education policy
Keywords: rola dyrektora szkoły; przywództwo w edukacji; zarządzanie szkołą; polityka oświatowa; partnerstwo edukacyjne